2004
DOI: 10.1128/iai.72.6.3398-3409.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of theicmHandicmFGenes Required forLegionella pneumophilaIntracellular Growth, Genes That Are Present in Many Bacteria Associated with Eukaryotic Cells

Abstract: Legionella pneumophila, the causative agent of Legionnaires' disease, replicates intracellularly within a specialized phagosome of mammalian and protozoan host cells, and the Icm/Dot type IV secretion system has been shown to be essential for this process. Unlike all the other known Icm/Dot proteins, the IcmF protein, which was described before, and the IcmH protein, which is characterized here, have homologous proteins in many bacteria (such as Yersinia pestis, Salmonella enterica, Rhizobium leguminosarum, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 72 publications
5
50
0
2
Order By: Relevance
“…However, inactivation of three other dot/icm genes-icmF, dotU, and icmR-did suppress loss of dotL (Fig. 6), even though loss of these genes caused only a partial inhibition of growth in permissive hosts (12,53,54,62,68). These results indicate that, although inactivation of the majority of the dot/icm genes can suppress the lethality caused by loss of dotL, there is specificity to the suppression.…”
Section: Figmentioning
confidence: 68%
“…However, inactivation of three other dot/icm genes-icmF, dotU, and icmR-did suppress loss of dotL (Fig. 6), even though loss of these genes caused only a partial inhibition of growth in permissive hosts (12,53,54,62,68). These results indicate that, although inactivation of the majority of the dot/icm genes can suppress the lethality caused by loss of dotL, there is specificity to the suppression.…”
Section: Figmentioning
confidence: 68%
“…6, in trans expression of the cloned dsbB gene provided nearly complete complementation of the virulence defect in three different cell types. Further analysis showed that the LD 50 was 60.25 CFU, which is comparable to the wild-type LD 50 (66.25 CFU).…”
Section: Each F Novicida Mutant Harbored a Single Transposon Insertionmentioning
confidence: 79%
“…Based on its in vitro growth defect, comparatively low LD 50 , relative lack of intracellular attenuation, and questionable dissemination patterns, we felt that the carB mutant was not a strong enough candidate to include in further development of a vaccine against tularemia, and therefore we did not attempt to complement the carB gene.…”
Section: Each F Novicida Mutant Harbored a Single Transposon Insertionmentioning
confidence: 99%
“…dotU and icmF mutants have similar intracellular growth phenotypes, i.e. partially defective in replication within macrophages (Sexton et al, 2004;Zusman et al, 2004), which suggested that the DotU and IcmF proteins worked together. Furthermore, the lack of IcmF resulted in a reduced level Fig.…”
Section: The Dotu/icmf Paradigmmentioning
confidence: 89%